Implementasi Branding Dan Digitalisasi Bisnis Pada UMKM Di Wilayah Klampok Kota Blitar - Syifana, Ananda Azza; Puspitasari, Sekar Aulia; Afifah, Nur; Sawitri, Dewi Khrisna (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
In this journal, the authors will discuss Branding and Digitalization in UMKM in the Klampok Village, Sananwetan District, Blitar City. This journal will discuss in detail what branding and digitization are that we will apply to UMKM in this Klampok village. Branding itself is an attempt to provide a company with a certain design or symbol as an identity in a business or company. Branding is usually synonymous with logos, designs, packaging, brands, etc. Branding is very important because branding can create an impression on consumers so they can find out what the company expects. In addition, Branding is also a way to differentiate yourself from performance competitors or other companies. Digitalization is a process of change that is analog to digital technology. This digitalization is also a framework for increasing the efficiency and effectiveness of performance in each section. The digitalization that we are doing is more focused on digitalizing marketing, digitizing marketplaces, digitizing social media and also creating websites for the UMKM we assist. The Branding and Digitalization that we do is of course to help the UMKM that we assist can develop properly.